Bee Pollen and Bee Bread as a Source of Bacteria Producing Antimicrobials - Karolina Pełka; Randy W. Worobo; Justyna Walkusz; Piotr Szweda (MDPI AG, 2021)
The principal objective of the study was the isolation and identification of bacteria that are present in mature bee bread (BB) and dried (ready for selling and consumption) bee pollen (BP). Obtained isolates were screened for their potential to inhibit select human pathogenic bacteria and their ability to produce enzymes of particular industrial importance. Four and five samples of BP and BB, respectively, were used for the study. In total, 81 strains of bacteria were isolated, and 34 (42%) of them exhibited antagonistic interactions with at least one reference strain of pathogenic bacteria, namely Staphylococcus aureus ATCC 25923, Staphylococcus aureus ATCC 29213, Staphylococcus epidermidis 12228, Pseudomonas aeruginosa ATCC 27857, and Escherichia coli ATCC 25922. The sequencing of the 16S rRNA gene revealed that all strains producing antimicrobials belong to the genus Bacillus spp., and among them, five species were identified: B. pumilus (n = 17), B. altitudinis (n = 9), B. licheniformis (n = 4), B. subtilis (n = 2), and B. safensis (n = 1). Furthermore, 69, 54, 39, and 29 of the strains exhibited lipolytic, proteolytic, cellulolytic, and esterolytic activity, respectively. Alpha amylase and beta galactosidase activity were rarely observed, and none of the strains produced laccase. The outcomes of the study revealed that BP and BB can be considered potential sources of bacteria producing antimicrobial agents and/or enzymes of particular industrial importance. Of course, additional research is required to verify this hypothesis, but the results of preliminary studies are promising.